AVALIAÇÃO DE CARACTERÍSTICAS CLÍNICAS E LABORATORIAIS COMO FATORES PREDITIVOS NO PERÍODO DE INDUÇÃO DO TRATAMENTO DE PACIENTES COM LEUCEMIAS AGUDAS - Camelo, Nivânia Lisboa (2012)
Background: The recent WHO classification incorporates immunophenotypic and cytogenetic characteristics that have prognostic impact. Several studies have attempted to identify clinical, biological and laboratory findings that correlate with prognosis, in order to incorporate them within the risk classification system used to define the therapeutic strategy. This work was done since there is no study in our state correlating the clinical and laboratory variables to specific immunological as predictive factors in the treatment of patients with acute leukemia. Objective: To evaluate the predictive value of different markers in PB (peripheral blood) and BM (bone marrow) in the induction period of treatment and disease-free survival in patients with acute leukemia. Methods: We evaluated 110 patients diagnosed with acute leukemia by immunophenotyping. In PB were analyzed: the percentage of blasts, leukocyte count and platelets and hemoglobin, and percentage of blasts in BM, all at diagnosis and after treatment in order to evaluate the therapeutic response. Results: Of 110 patients 61.82% were male. Most (80.9%) was framed in the age group of children and adolescents. As for the subgroups of acute leukemias 61.82% of ALL patients had type B, 12.73% of ALL type T and 25.45% of AML. The percentage of blasts in BM and PB for each of the sub groups of leukemia during induction treatment showed no significant difference on the other hand, in a comparative study between the subgroups of leukemia, there was a difference in their standard of presentation to diagnosis. For T-ALL platelet count on the initial induction period (D0) showed significant difference for patients who relapsed after the induction period. Regarding AML, patients with lower hemoglobin on D0 showed a significant tendency to relapse after the induction period. The recovery of platelet count to LLA B at the last day of the induction period of the treatment to values above 100,000/mm³ is not pointed to the recurrence of the disease follow-up period. Conclusion: The percentage of blasts in BM and PB not shown to have predictive value in respect of reference of each of these groups of leukemia in the induction phase of treatment. Platelet counts below 100.000/mm3 in T-ALL seem to D0 have predictive value for recurrence of disease after the induction period of treatment. For AML, patients with lower Hb determination on D0 were more likely to relapse after the induction period. The CD10 antigen expression at diagnosis of the disease should be a marker of good prognosis for remission induction phase of treatment. For ALL B, platelet counts above 100.000/mm3 in the D29 demonstrated predictive value for maintenance of non-recurrence of disease after D29.